Transplacentally Transmitted Congenital Brucellosis due to Brucella abortus Biotype 1 in Sprague-Dawley Rats: Transplacentally Transmitted Congenital Brucellosis - Rahman, M. S.; Baek, B. K. (Biological Sciences - PJSIR, 2008)
In the investigation on the transplacentally transmitted congenital brucellosis due to Brucella abortus bio- type 1 in Sprague- Dawley rats, neither any stillbirth, abortion or premature birth nor any abnormality of fetus was observed in the infected group or in the control group. B. abortus biotype 1 was isolated from the fetus of infected rats only. Only one band of 498 base pair DNA was obtained in polymerase chain reaction products from DNA of the fetuses of infected SD rats.